An Efficient Synthesis of Fused 2‐Aryliminothiazolines via a Solvent‐Free Cyclopropyliminium Rearrangement. Issue 10 (7th July 2016) - Samet, Alexander V.; Silyanova, Evgenia A.; Semenova, Marina N.; Karnoukhova, Valentina A.; Semenov, Victor V.
Abstract: ( Z )‐3‐Aryliminopyrrolo[ 1, 2‐c ]thiazoles were prepared by a base‐induced dehydrobromination of 3‐arylaminopyrrolo[ 1, 2‐c ]thiazolium bromides, which, in turn, were obtained via an efficient solvent‐free cyclopropyliminium rearrangement of the corresponding 4‐cyclopropylthiazole hydrobromides proceeding in melt at high rate and in excellent yields. Biological evaluation using phenotypic sea urchin embryo assay showed that 2‐arylamino‐4‐cyclopropylthiazoles displayed an antimitotic tubulin‐unrelated activity, whereas fused‐ring rearrangement products were proposed to inhibit Ca‐Zn–dependent metalloproteases. Abstract : 3‐Arylaminopyrrolo[ 1, 2‐c ]thiazolium bromides, prepared via a solvent‐free high‐yielding cyclopropyliminium rearrangement of the corresponding 4‐cyclopropylthiazole hydrobromides, undergo base‐induced dehydrobromination to yield ( Z )‐3‐aryliminopyrrolo[ 1, 2‐c ]thiazoles.